Effectiveness of Low-Dose Intermittent Epidural Bolus of 1 mg Morphine as Postoperative Analgesia - Gusti Ayu Pitria Septiani (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2023)
Background: Patients who have undergone major surgery typically experience postoperative pain that persists for seven days following surgery. The challenge for the anesthesiologist is to provide adequate postoperative pain control which is not always achievable. In contrast to systemic administration, epidural administration of opioids places the medications close to the site of action, allowing for relatively small doses to be effective with a low incidence of side effects. Morphine is a long-established analgesia drug that characteristically slows diffusion and long duration in epidural analgesia, making it widely used in postoperative pain management. However, giving morphine is not without any complications.Case Illustration: Nine patients who underwent major surgeries either under combined epidural-general anesthesia or epidural anesthesia received a low-dose intermittent epidural bolus of 1 mg morphine in 10 mL normal saline every 12 hours after surgery. Postoperative pain scores were recorded at the 1st,12th,24th, 36th, and 48th hours after surgery, data of additional rescue analgesia, and the incidence of nausea, vomiting, pruritus, sedation, and respiratory depression were also collected. Only one patient needed rescue analgesia with 30 mg Ketorolac IV, and one patient needed anti-emetic with 4 mg ondansetron IV an hour after the completion of surgery. The rest of the patients have mild pain (NRS≤3/10) within 48 hours after surgery. Furthermore, there is no other adverse effects of morphine were foundConclusion: low dose intermittent epidural bolus of 1 mg morphine can be used as effective postoperative analgesia and has fewer adverse effects.